Comparison of the emissions and performance of ethanol-added diesel-biodiesel blends in a compression ignition engine with those of pure diesel - Klajn, Felipe Fernandes (Environmental technology, 2020)
In this study, a biodiesel was produced from blending vegetable and animal sources with diesel and diesel-ethanol using a motor-generator set to evaluate its performance and emission characteristics. Fifteen and twenty percent of animal-vegetable biodiesel were added to each diesel-ethanol blend. A motor-generator test was conducted for each mixture; each sample was subjected to resistive loads from 2 to 5 kW with six repetitions. The physicochemical properties met the national standard guidelines, while the best specific fuel consumption (SFC) was observed for the 15% biodiesel-1% ethanol (B15E1) blend at the load of 5 kW with 327.069 g kW-1 h-1, followed by diesel (334.875 g kW-1 h-1). The exhaust gas temperature behaved differently depending on the ethanol concentration; it was lower when the concentration of added ethanol was higher. The NO emissions decreased while the SO2 emissions increased as the ethanol concentration increased